2015
DOI: 10.1209/0295-5075/111/67005
|View full text |Cite
|
Sign up to set email alerts
|

Strain-controlled spin and charge pumping in graphene devices via spin-orbit coupled barriers

Abstract: -We theoretically propose a graphene-based adiabatic quantum pump with intrinsic spin-orbit coupling (SOC) subject to strain where two time-dependent extrinsic spin-orbit coupled barriers drive spin and charge currents. We study three differing operation modes where i) location, ii) chemical potential, and iii) SOC of the two barriers oscillate periodically and out of phase around their equilibrium states. Our results demonstrate that the amplitude of adiabatically pumped currents highly depends on the conside… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…For example, the interplay of massive electrons with spin orbit coupling in the presence of strain in a graphene layer yields controllable spatially separated spin-valley filtering 38,39 . Therefore, this property can be employed as a means to control the spin-transport graphene-based spintronics devices 46 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the interplay of massive electrons with spin orbit coupling in the presence of strain in a graphene layer yields controllable spatially separated spin-valley filtering 38,39 . Therefore, this property can be employed as a means to control the spin-transport graphene-based spintronics devices 46 .…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 12, we see that (30) will coincide with the left part of Fig. 11 much better for the case N = 1/20.…”
Section: Fig 11mentioning
confidence: 69%
“…These results promise practical applications of the graphitic nanocones in close future. New calculations related to the spin-orbital coupling in graphene [30] as well as the theoretical and experimental investigations of graphene monolayer and bilayer from the last days [31,32] contribute to this goal.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Also, spin pumping in graphene devices [13][14][15][16][17][18] and adiabatic pumping [19][20][21] were studied recently. It has been reported that the quantized current pumping can be achieved by applying periodic voltage modulation on a quantum dot gate.…”
Section: Introductionmentioning
confidence: 99%